The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/membranes11050318
|View full text |Cite
|
Sign up to set email alerts
|

Block Copolymer Template-Directed Catalytic Systems: Recent Progress and Perspectives

Abstract: Fabrication of block copolymer (BCP) template-assisted nano-catalysts has been a subject of immense interest in the field of catalysis and polymer chemistry for more than two decades now. Different methods, such as colloidal route, on-substrate methods, bulk self-assembly approaches, combined approaches, and many others have been used to prepare such nano-catalysts. The present review focuses on the advances made in this direction using diblock, triblock, and other types of BCP self-assembled structures. It wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Block copolymers composed of more than one species of monomer linked by chemical bonds have also been used as chiral assemblies. 35 The morphologies of block copolymers depend on the thermal equilibrium condition with respect to the volume fraction of monomer blocks. Thus, various morphologies, such as lamellae and cylinders, and even chiral geometries, like gyroid, 36,37 spiral, 38–40 toroid, 41 and helix, can be obtained by exploiting phase separation and reconstructions of block copolymers.…”
Section: Part 1 3d Self-assembly For Fabrication Of Chiral Metamaterialsmentioning
confidence: 99%
“…Block copolymers composed of more than one species of monomer linked by chemical bonds have also been used as chiral assemblies. 35 The morphologies of block copolymers depend on the thermal equilibrium condition with respect to the volume fraction of monomer blocks. Thus, various morphologies, such as lamellae and cylinders, and even chiral geometries, like gyroid, 36,37 spiral, 38–40 toroid, 41 and helix, can be obtained by exploiting phase separation and reconstructions of block copolymers.…”
Section: Part 1 3d Self-assembly For Fabrication Of Chiral Metamaterialsmentioning
confidence: 99%
“…Block copolymers (BCPs) have gained remarkable attention as crucial materials for controlling the spatial positioning of various types as well as multiple types of nanoparticles. For example, Haridas and Basu have demonstrated the fabrication of hybrid arrays comprising CdSe QDs and AuNPs using BCP thin films as templates. Lü et al have demonstrated a quick and efficient way to precisely control the dispersion and localization of QDs in BCP micelles via coordination interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, self-assembly of rod-rod BCPs was rarely studied because of severe polymerization conditions. Spherical micelles and vesicles could be easily obtained via self-assembly of coil-coil BCPs, showing extensive applications as templates, 5,6 catalysts, 7,8 nanoreactors, 9,10 etc. However, the phase region of the nonspherical morphologies is extremely narrow, 11 which restricts some morphology-dependent applications in biomedicine, [12][13][14] stimuliresponsive materials, [15][16][17][18][19] controlled drug delivery systems, 20,21 and so on.…”
Section: Introductionmentioning
confidence: 99%